Прогнозування вибору методу оперативного втручання при ускладнених псевдокістах підшлункової залози третього типу = Forecasting method of choice of surgical intervention in complicated pancreatic pseudocysts third type - I. A. Kryvorychko; N. M. Goncharova; O. V. Arsenуev (Kazimierz Wielki University, 2016)
Kryvorychko І. А., Goncharova N. M., Arsenуev O. V. Прогнозування вибору методу оперативного втручання при ускладнених псевдокістах підшлункової залози третього типу = Forecasting method of choice of surgical intervention in complicated pancreatic pseudocysts third type. Journal of Education, Health and Sport. 2016;6(6):59-68. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.54600 http://ojs.ukw.edu.pl/index.php/johs/article/view/3544     The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 25.05.2016.   УДК 616.37-006.2-036.17-073-074-089.87(043.3)   Прогнозування вибору методу оперативного втручання при ускладнених псевдокістах підшлункової залози третього типу   1І. А. Криворучко, 1Н. М. Гончарова, 2О. В. Арсен'єв   1 Харківський національний медичний університет МЗ України, м. Харків 2 Харківський національний фармацевтичний університет, кафедра фармакоінформатики, м. Харків   Резюме. З метою покращення якості життя хворих, оперованих з приводу ускладнених псевдокист підшлункової залози третього типу за класифікацією D'Egidio A. та Schein M. (1991), проаналізовані результати хірургічних втручань 52 пацієнтів. Для моделювання та прогнозування вибору метода хірургічного лікування використовувалися багатовимірні статистичні методи: агломеративний та дивізимний кластерний аналіз, дискримінантний аналіз, дерева класифікації. Вибір виду операції в залежності від результату лікування визначався максимальним значенням «кваліфікаційної» функції в стовпці. Проведення лапаротомії для псевдокист підшлункової залози третього типу з максимальною ймовірністю закінчиться результатом 3 (до 21 ліжко-дня без післяопераційних ускладнень) або результатом 1 (до 14 ліжко-дня без післяопераційних ускладнень) з втричі меншою ймовірністю. При проведенні мініінвазивних операцій характерний результат 1 (до 14 ліжко-дня без післяопераційних ускладнень) або 3 (до 21 ліжко-дня без післяопераційних ускладнень), в два рази меньшою ймовірністю. Таким чином, для лікування ускладнених псевдокист підшлункової залози третього типу найбільш доцільним є використання мініінвазивних методик. Ключові слова: ускладнені псевдокісти підшлункової залози, прогноз, статистичні методи, мініінвазивні втручання, лапаротомні втручання.           Forecasting method of choice of surgical intervention in complicated pancreatic pseudocysts third type   1 І. А. Kryvorychko, 1 N. M. Goncharova, 2 O. V. Arsenуev   1 Kharkiv national medical university, Kharkiv 2  Kharkiv National University of Pharmacy, Department of pharmacoinformatics, Kharkiv   Summary. In order to improve the quality of life of patients operated on for complicated pancreatic pseudocysts third type according to the classification D'Egidio A. and Schein M. (1991), analyzed the results of 52 surgical patients. For the simulation and prediction of the selection method of surgical treatment used multivariate statistical techniques: agglomerative and cluster analysis, discriminant analysis, classification trees. Choosing the type of surgery, depending on the outcome of treatment is determined by the maximum value of "qualification" in the column functions. Carrying laparotomy for pancreatic pseudocysts third type with maximum probability end result of 3 (up to 21 beds a day without postoperative complications), or the result of 1 (up to 14 beds a day without postoperative complications), three times less likely. During the minimally invasive operations of typical result 1 (up to 14 days without a bed after surgical complications) or 3 (up to 21 beds a day without postoperative complications), twice as less likely. Thus, for the treatment of complicated pancreatic pseudocysts third type most rational use of minimally invasive techniques.   Keywords: complicated pancreatic pseudocyst, forecast, statistical methods, minimally invasive intervention, laparotomic intervention.           Прогнозирование выбора метода оперативного вмешательства при осложненных псевдокистах поджелудочной железы третьего типа   1 И. А. Криворучко, 1 Н. Н. Гончарова, 2 А. В. Арсеньєв   1 Харьковский национальный медицинский университет МЗ Украины, г. Харьков 2 Харьковский национальный фармацевтический унивеситет, кафедра фармакоинформатики, г. Харьков   Резюме. С целью улучшения качества жизни больных, оперированных по поводу осложненных псевдокист поджелудочной железы третього типа согласно классификации D'Egidio A. и Schein M. (1991), проанализированы результаты хирургических вмешательств 52 пациентов. Для моделирования и прогнозирования выбора метода хирургического лечения использовались многомерные статистические методы: агломеративный и дивизимный кластерный анализ, дискриминантный анализ, деревья классификаций.